(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of the present study was to evaluate heterozygosis in cattle population, and to characterize White Fulani breed by identifying DNA markers considering microsatellites. Materials and Methods: A total of 41 cattle were randomly selected and used for sample (wool) collection for the characterization and identification of phenotypic traits of cattle in Nigeria. The DNA samples from the samples were prepared. Twelve microsatellite primers were used for the microsatellite analysis in the genomic DNA of cattle. The reinforced products were analyzed to determine polymorphic alleles and their frequencies. Results: White Fulani is characterized by a high degree of genetic diversity. The microsatellites have multiple alleles and may show heterozygosity frequencies of at least 70%. White Fulani cows and their F1 descendants form a common cluster, to which the bulls of the Kuru and Red Boro breeds are adjacent. There is a clear differentiation of purebred populations of Tajik zebu-like cattle (Q = 98.7%) and a significant proportion of white Fulani (Q = 81.8%) from Nigeria. The microsatellite analysis of zebu of Nigeria allowed identifying a total of 80 alleles. In the KURU and PAX-KR-BOR rocks, 17 and 19 alleles were identified, respectively. In F1, 51 alleles were detected. Conclusion: White Fulani cattle are characterized by a high degree of genetic diversities. This makes it a highly informative source in genetic analysis. The results can be applied in dealing with the conservation and sustainable applications of genetic resources in the Nigerian cattle population. J. Adv. Vet. Anim. Res., 6(4): 474-480, December 2019